Optimal. Leaf size=23 \[ e^{\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}} \]
________________________________________________________________________________________
Rubi [F] time = 1.98, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {\exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right ) \left (-6+e^{1+x+x^2} \left (-3 x-6 x^2\right )\right )}{1568 x^3} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int \frac {\exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right ) \left (-6+e^{1+x+x^2} \left (-3 x-6 x^2\right )\right )}{x^3} \, dx}{1568}\\ &=\frac {\int \left (-\frac {6 \exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right )}{x^3}-\frac {3 \exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right ) (1+2 x)}{x^2}\right ) \, dx}{1568}\\ &=-\frac {3 \int \frac {\exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right ) (1+2 x)}{x^2} \, dx}{1568}-\frac {3}{784} \int \frac {\exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right )}{x^3} \, dx\\ &=-\frac {3 \int \left (\frac {\exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right )}{x^2}+\frac {2 \exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right )}{x}\right ) \, dx}{1568}-\frac {3}{784} \int \frac {\exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right )}{x^3} \, dx\\ &=-\frac {3 \int \frac {\exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right )}{x^2} \, dx}{1568}-\frac {3}{784} \int \frac {\exp \left (-1-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}\right )}{x^3} \, dx-\frac {3}{784} \int \frac {\exp \left (-e^{1+x+x^2}+\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}+x+x^2\right )}{x} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.64, size = 23, normalized size = 1.00 \begin {gather*} e^{\frac {3 e^{-1-e^{1+x+x^2}}}{1568 x^2}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [B] time = 0.81, size = 47, normalized size = 2.04 \begin {gather*} e^{\left (-\frac {1568 \, x^{2} e^{\left (x^{2} + x + 1\right )} + 1568 \, x^{2} - 3 \, e^{\left (-e^{\left (x^{2} + x + 1\right )} - 1\right )}}{1568 \, x^{2}} + e^{\left (x^{2} + x + 1\right )} + 1\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int -\frac {3 \, {\left ({\left (2 \, x^{2} + x\right )} e^{\left (x^{2} + x + 1\right )} + 2\right )} e^{\left (\frac {3 \, e^{\left (-e^{\left (x^{2} + x + 1\right )} - 1\right )}}{1568 \, x^{2}} - e^{\left (x^{2} + x + 1\right )} - 1\right )}}{1568 \, x^{3}}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.09, size = 19, normalized size = 0.83
method | result | size |
risch | \({\mathrm e}^{\frac {3 \,{\mathrm e}^{-{\mathrm e}^{x^{2}+x +1}-1}}{1568 x^{2}}}\) | \(19\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.61, size = 18, normalized size = 0.78 \begin {gather*} e^{\left (\frac {3 \, e^{\left (-e^{\left (x^{2} + x + 1\right )} - 1\right )}}{1568 \, x^{2}}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 8.75, size = 19, normalized size = 0.83 \begin {gather*} {\mathrm {e}}^{\frac {3\,{\mathrm {e}}^{-{\mathrm {e}}^{x^2}\,\mathrm {e}\,{\mathrm {e}}^x}\,{\mathrm {e}}^{-1}}{1568\,x^2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 1.00, size = 20, normalized size = 0.87 \begin {gather*} e^{\frac {3 e^{- e^{x^{2} + x + 1} - 1}}{1568 x^{2}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________